A tiny new species of leaf insect (Phasmatodea, Phylliidae) from New Guinea - Kamp, Thomas De Van; Hennemann, Frank H. (Zootaxa, 2014)
The female and egg of the new Papuan leaf insect Phyllium (Phyllium) riedeli n. sp. are described and illustrated. The species belongs in the siccifolium species-group of the subgenus Phyllium and, with a body length of 56.3 mm, represents the smallest leaf insect so far described for the genus. The type-specimens are stored in the State Museum of Natural History Karlsruhe, Germany (SMNK). A checklist and key is provided for the New Guinean representatives of Phyllium (Phyllium) Illiger, 1798.